Extrafoveally applied flashing light affects contrast thresholds of achromatic and S-cone isolating, but not L-M cone modulated stimuli - Őze, A.; Puszta, A.; Buzás, P.; Kóbor, P.; Braunitzer, G.; Nagy, A. (Neuroscience letters, 2018)
•Calibrated isoluminant chromatic and achromatic stimuli were applied.•Light flashes influence both chromatic and achromatic color contrast thresholds.•Peripheral flicker effect influences the detection of S-cone isolating stimuli.•Achromatic thresholds are the most strongly affected by light flashes. Flashing light stimulation is often used to investigate the visual system. However, the magnitude of the effect of this stimulus on the various subcortical pathways is not well investigated. The signals of conscious vision are conveyed by the magnocellular, parvocellular and koniocellular pathways. Parvocellular and koniocellular pathways (or more precisely, the L-M opponent and S-cone isolating channels) can be accessed by isoluminant red-green (L-M) and S-cone isolating stimuli, respectively. The main goal of the present study was to explore how costimulation with strong white extrafoveal light flashes alters the perception of stimuli specific to these pathways. Eleven healthy volunteers with negative neurological and ophthalmological history were enrolled for the study. Isoluminance of L-M and S-cone isolating sine-wave gratings was set individually, using the minimum motion procedure. The contrast thresholds for these stimuli as well as for achromatic gratings were determined by an adaptive staircase procedure where subjects had to indicate the orientation (horizontal, oblique or vertical) of the gratings. Thresholds were then determined again while a strong white peripheral light flash was presented 50 ms before each trial. Peripheral light flashes significantly (p < 0.05) increased the contrast thresholds of the achromatic and S-cone isolating stimuli. The threshold elevation was especially marked in case of the achromatic stimuli. However, the contrast threshold for the L-M stimuli was not significantly influenced by the light flashes. We conclude that extrafoveally applied light flashes influence predominantly the perception of achromatic stimuli.